Kecerdasan Kinestetik Pada Anak Usia Dini - Rahmasanti, Heliani; Nurhasanah, Cindi Mulia; Monica, Yunsia Bella (MENTARI: Jurnal Pendidikan Anak Usia Dini, 2025)
Intelligence is the ability to create a form of skill that exists within a person, to find a way out of the problems faced in the form of new understanding. Every child has different intelligence, one of which is kinesthetic intelligence. This type of research uses a type of library or library research. Meanwhile, the data collection technique used is literature data collection. The development of kinesthetic intelligence can develop well, influenced by several factors including; (1) supporting factors such as parental support and the environment, as well as obstacles such as lack of guidance and negative environmental influences (2) strategies that can be used to develop kinesthetic intelligence, including training on coordination, balance, flexibility and endurance.